Pengaruh Persepsi Korupsi Pajak dan Kualitas Pelayanan Fiskus terhadap Kepatuhan Wajib Pajak Orang Pribadi - klarista widya; Maryani Maryani; Arif Makhsun (Reviu Akuntansi, Manajemen, dan Bisnis, 2022)
Purpose: This study aimed to determine the effect of tax corruption perception and service quality tax officer towards individual taxpayers compliance in Lampung Province. Method: The sampling method used is proportional random sampling with a sample of 130 individual taxpayers registered at 6 KPP’s in Lampung Province. The analytical tool used in this research is multiple linear regression analysis. Data were analyzed using SPSS version 22. Results: The results of this study show that tax corruption perception has positif and significant effect on individual taxpayers compliance in Lampung Province and service quality tax officer has no effect on individual taxpayers compliance in Lampung Province. Limitations: This study only uses two independent variables while there are many other variables that can affect taxpayer compliance. Contribution: This study is expected to provide information for the KPP regarding the effect of service quality and the effect of tax corruption perception on taxpayer compliance.